ANALISIS KINERJA KEUANGAN DAERAH PEMERINTAH KOTA SURABAYA TAHUN 2015-2019 - Nuzulul Siswo Abdulaziz; Betty Silfia Ayu Utami (Journal of Economics Development Issues, 2021)
This study will answer questions about the level of efficiency and effectiveness of the Surabaya City Government's regional finance for the 2015-2019 fiscal year and how the level of regional financial independence of the Surabaya City Government for the 2015-2019 fiscal year. This study uses a descriptive research method with a quantitative approach. The data used is secondary data that comes from the website of the Surabaya City Financial and Regional Tax Management Agency. The data analysis technique uses financial ratios. The results of this study are the level of efficiency shows that the regional finances of the Surabaya City Government for the 2015-2019 fiscal year are classified as less efficient and inefficient, because the efficiency ratio is between 90%-100% and more than 100%. The level of effectiveness of the performance of the Surabaya City Government is included in the very effective category in managing the realization of Surabaya City's revenue, the average is above 100%. Judging from the level of regional financial independence, it shows that the level of dependence of the Surabaya City Government on the Central Government is delegative, ie there is no intervention from the Central Government, because the average value of regional financial independence is 166.23%. Keywords: Regional Financial Performance, Efficiency, Effectiveness and Independence of Regional Finance. Penelitian ini akan menjawab pertanyaan tentang bagaimana tingkat efisiensi dan tingkat efektivitas keuangan daerah Pemerintah Kota Surabaya tahun anggaran 2015-2019 dan bagaimana tingkat kemandirian keuangan daerah Pemerintah Kota Surabaya tahun anggaran 2015-2019. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kuantitatif. Data yang digunakan ialah data sekunder yang berasal dari situs web Badan Pengelolaan Keuangan dan Pajak Daerah Kota Surabaya. Teknik analisis data menggunakan rasio keuangan. Hasil penelitian ini ialah tingkat efisiensi menunjukkan keuangan daerah Pemerintah Kota Surabaya Tahun anggaran 2015-2019 tergolong kurang efisien dan tidak efisien, karena rasio efisiensi berada antara 90%-100% dan lebih dari 100%. Tingkat efektivitas kinerja Pemerintah Kota Surabaya masuk pada kategori sangat efektif dalam pengelolaan realisasi pendapatan Kota Surabaya, rata-rata berada diatas 100%. Ditinjau dari tingkat kemandirian keuangan daerah menunjukkan bahwa tingkat ketergantungan Pemerintah Kota Surabaya terhadap Pemerintah Pusat termasuk delegatif, yakni tidak ada campur tangan Pemerintah Pusat, dikarenakan nilai rata-rata kemandirian keuangan daerah 166,23%. Kata Kunci: Kinerja Keuangan Daerah, Efisiensi, Efektivitas dan Kemandirian Keuangan Daerah